Effect of Seed Pelleting with Microbial and Organic Filler Materials on Growth and Yield of Linseed (Linum usitatissimum L.) - RACHANA HS; SR DODDAGOUDAR; BS GANIGARA; SANGEETA I MACHA; N ANANDA (Seed Research, 2025)
Linseed (Linum usitatissimum L.) is an important oilseed crop, but its small seed size often hampersuniform sowing and seedling establishment. Seed pelleting is an effective technique to enhance seed handling,precision planting, and delivery of beneficial bio-inoculants. A field experiment was conducted to evaluate theeffect of different pelleting materials on emergence, growth, yield, and yield attributes of linseed. Eight treatmentscomprising microbial inoculants (Trichoderma viride, Azospirillum brasilense, Metarhizium anisopliae), organicleaf powders (Pongamia pinnata, Prosopis juliflora, Azadirachta indica), fly ash, and an unpelleted control weretested in a randomized block design with three replications. Seed pelleting significantly improved crop performancecompared to the control. Pelleting with Metarhizium anisopliae at a 1:3 ratio recorded the highest field emergence(98.25%), plant height (42.93 cm), number of branches (5.47), capsules per plant (39.94), 1000-seed weight(8.66 g), seed yield per plant (1.83 g), and yield per hectare (894 kg ha-¹). The unpelleted control showed thelowest values for all parameters. The study concludes that microbial-based pelleting with Metarhizium anisopliaeis an effective and eco-friendly strategy to enhance seedling vigour, crop establishment, and productivity of linseed.